Comparative genome analysis of Burkholderia phytofirmans PsJN reveals a wide spectrum of endophytic lifestyles based on interaction strategies with host plants - Mitter, Birgit; Petric, Alexandra; Shin, Maria W.; Chain, Patrick S.; Hauberg-Lotte, Lena; Reinhold-Hurek, Barbara; Nowak, Jerzy; Sessitsch, Angela (Frontiers in Plant Science, 2013)
Burkholderia phytofirmans PsJN is a naturally occurring plant-associated bacterial endophyte that effectively colonizes a wide range of plants and stimulates their growth and vitality. Here we analyze whole genomes, of PsJN and of eight other endophytic bacteria. This study illustrates that a wide spectrum of endophytic life styles exists. Although we postulate the existence of typical endophytic traits, no unique gene cluster could be exclusively linked to the endophytic lifestyle. Furthermore, our study revealed a high genetic diversity among bacterial endophytes as reflected in their genotypic and phenotypic features. B. phytofirmans PsJN is in many aspects outstanding among the selected endophytes. It has the biggest genome consisting of two chromosomes and one plasmid, well equipped with genes for the degradation of complex organic compounds and detoxification, e.g. 24 glutathione-S-transferase genes. Furthermore, strain PsJN has a high number of cell surface signaling and secretion systems and harbors the 3-OH-PAME quorum-sensing system that coordinates the switch of free-living to the symbiotic lifestyle in the plant-pathogen R. solanacearum. The ability of B. phytofirmans PsJN to successfully colonize such a wide variety of plant species might be based on its large genome harboring a broad range of physiological functions.